Climate-induced risks, adaptation, and mitigation responses: a comparative study on climate-stressed coastal communities - Swarnokar, Sadhon Chandra; Mou, Sadia Islam; Sharmi, Sutapa Dey; Iftikhar, Afif; Jesmin, Sabrina (Frontiers in Climate, 2025)
IntroductionTildanga, Kamarkhola, and Sutarkhali under Dacope Upazila of Bangladesh are climate-stressed coastal unions, highly susceptible to recurrent hydroclimatic challenges and anthropogenic interruptions such as cyclones, storm surges, flooding, waterlogging, salinity intrusion, and erratic rainfall. These challenges significantly impact water resources, agriculture, and prevailing livelihoods. Given the increasing vulnerability of coastal communities, it is crucial to understand local perceptions of climate hazards, their socio-economic impacts, and the adaptation and mitigation strategies implemented to enhance coastal resilience.MethodsThis study adopts a mixed-method approach, incorporating 150 structured questionnaire surveys, six focus group discussions, 15 key informant interviews, and 15 in-depth interviews. The research explores community perceptions of climate risks, grassroots innovations, and adaptive responses aimed at mitigating the adverse effects of climate change.ResultsFindings indicate that communities have adopted various strategies to combat coastal challenges, including climate-resilient agriculture, rainwater harvesting, homestead vegetation, mixed cropping with fish culture, opting for saline-tolerant varieties, elevated housing, and disaster preparedness measures. However, financial limitations, inadequate technical knowledge, lack of proper training, and institutional gaps hinder the sustainability and scalability of these strategies. For instance, although solar power-based water management and climate-resilient infrastructure have proven effective, their implementation remains restricted due to resource limitations and inadequate stakeholder participation. Additionally, a gender-responsive approach has empowered women as key contributors to household resilience and inclusive adaptation strategies.DiscussionA comparative analysis reveals that Kamarkhola is more vulnerable to cyclones and floods, whereas Tildanga and Sutarkhali are primarily affected by salinity intrusion. The study further examines the effectiveness of governance in addressing adaptation rates, livelihood and occupational patterns, increasing water stress, and declining agricultural productivity. Addressing these gaps is essential for strengthening climate resilience and ensuring human security. Finally, the study advocates for policy recommendations that integrate local knowledge, enhance institutional support, and foster community engagement to promote long-term resilience and socio-economic stability in these climate-vulnerable regions.